Sistem Pendukung Keputusan Penerimaan Dosen Tetap Menggunakan Metode MOORA dan MOSRA - Mesran Mesran; Rima Tamara Aldisa; Wanda Tofani Devi Rangkuti; Cindy Nanda Sari (Jurnal Sistem Komputer dan Informatika (JSON), 2023)
Lecturers are the forerunners and places to gain knowledge for the nation's children, good lecturers will produce good students too, and good students will become successors to the progress of the nation to be even better, the large number of lecturers at Budi Darma University results in a density of lecturers, it is important to do acceptance of permanent lecturers to provide rewards to lecturers who have worked diligently and earnestly, each lecturer has their own quality but permanent lecturers are lecturers who have a safer position and are trusted by the campus, the importance of selecting permanent lecturers using a system decision support to prevent fraud in the election process. In this study, the MOORA (Multi-Objective Optimization on the Basis Of Ratio Analysis) and MOOSRA (Multi-objective Optimization on the basis of Simple Ratio Analysis) methods are used to assist the selection process in a logical, systemic manner and can produce a decision value on the ranking value. which are different from each formula or algorithm, but these values are equally real and fair without any cheating. In this study the authors also used the ROC (Rank Order Centroid) value to obtain an effective and correct weighting value to perform calculations on the criteria values that had been set by the campus or college of the Budi Darma Medan University. The results in this study based on the calculation of the MOORA method, the highest result was achieved by A1, which is worth 0.4742 and in the MOOSRA method, the highest alternative result was achieved by A1, which is worth 28.1366.